Jogos e diversões infantis: um estudo geossociolinguístico na Região Norte do Brasil - FERREIRA, Josevaldo Alves (Universidade Federal do Pará, 2017)
This project aims to map and discuss the lexical semantic variaton in six states in the north region of Brazil in the cities that have been researched by the Linguistic Atlas of Brazil (ALiB), in order to demonstrate areas where common lexical itens may occur, compare the data from the small towns to the ones from the capital cities, in addition to making a comparison between the results from the north region to the ones from the baiano speaking area which has been researched by Ribeiro (2012). As theoretical support to the development of this Project we have considered the Pluridimensional Dialectology by Thun (1998), as well as the contributions made by professors like Cardoso (2010), Razky (2013). The Geolinguistic method has been followed in this Project, which presents the achieved results through the use of maps that show the geographical variation of the language. As this is a pluridimensional Project it will portray, through graphics, the diatopic and the diastratic variation like age and sex. In order to carry on with this study, it has been used ALiB Project data which have been collected in twenty three locations in the north region of Brazil in six different states. Subjects of both sex and two different age levels (18 to 35 years old and 50 to 65 years old) have been interviewed. To collect the data researchers have applied a lexical-semantic questionnaire made up of 202 questions which covers 14 semantic fields. However, this Project has limited itself to study the semantic field “childhood games and plays”. The results achieved show the occurrence of at least two different geographical areas where proper lexical itens may be found, that is, the northeast and the southeast of the north region of Brazil. The capital cities and the small towns demonstrated a few lexical differences in the studied semantic field. Some lexical itens which characterizes the north region thus differing it from the baiano speaking area are peteca, to name bolinha de gude, baladeira to estilingue and curica to pipa sem vareta just to name but a few.